PELATIHAN PEMANFAATAN FITUR PENJUALAN APLIKASI TOKOPEDIA PADA KADER USAHA PENINGKATAN PENDAPATAN KELUARGA (UP2K) PKK KELURAHAN KOTA BAMBU UTARA - Grace Gata; Wachyu Hari Haji; Anita Ratnasari (Jurnal Pengabdian Masyarakat Nasional, 2023)
Today's rapidly developing technology requires UP2K-PKK Cadre owners to try even harder to provide the best service to customers. Indonesia is experiencing a fairly high growth of internet users, where in 2013 there were around 40% of the total population of Indonesia. With the increase in internet users, the online market share is getting higher, and therefore marketing using internet media is quite promising because internet users are getting higher and also the area coverage is getting wider. By having knowledge about Utilizing the selling features of the Tokopedia application in the Tokopedia Application for Product Marketing, Micro, Small and Medium Enterprises (KADER UP2K-PKK) can sell their products even better.